Environmental risks associated with contaminants of legacy and emerging concern at European aquaculture areas. (September 2019) - Aminot, Yann; Sayfritz, Stephen J.; Thomas, Kevin V.; Godinho, Lia; Botteon, Elena; Ferrari, Federico; Boti, Vasiliki; Albanis, Triantafyllos; Köck-Schulmeyer, Marianne; Diaz-Cruz, M. Silvia; Farré, Marinella; Barceló, Damià; et al.
Abstract: The contamination of marine ecosystems by contaminants of emerging concern such as personal care products or per- and polyfluoroalkyl substances is of increasing concern. This work assessed the concentrations of selected contaminants of emerging concern in water and sediment of European aquaculture areas, to evaluate their co-variation with legacy contaminants (polycyclic aromatic hydrocarbons) and faecal biomarkers, and estimate the risks associated with their occurrence. The 9 study sites were selected in 7 European countries to be representative of the aquaculture activities of their region: 4 sites in the Atlantic Ocean and 5 in the Mediterranean Sea. Musks, UV filters, preservatives, per- and polyfluoroalkyl substances and polycyclic aromatic hydrocarbons were detected in at least one of the sites with regional differences. While personal care products appear to be the main component of the water contamination, polycyclic aromatic hydrocarbons were mostly found in sediments. As expected, generally higher levels of personal care products were found in sewage impacted sites, urbanised coasts and estuaries. The risk assessment for water and sediment revealed a potential risk for the local aquatic environment from contaminants of both legacy and emerging concern, with a significant contribution of the UV filter octocrylene. Despite marginal contributions of per- and polyfluoroalkyl substances to the total concentrations, PFOS (perfluorooctane sulfonate) aqueous concentrations combined to its low ecotoxicity thresholds produced significant hazard quotients indicating a potential risk to the ecosystems. Graphical abstract: Image 1 Highlights: 59 contaminants of legacy and emerging concern searched in 9 European aquaculture areas. Levels of personal care products were higher in sewage impacted zones. Hazard quotients revealed potential environmental risks from PAHs, PFAS and UV filters.